2018
DOI: 10.1111/cas.13712
|View full text |Cite
|
Sign up to set email alerts
|

Periostin and CA242 as potential diagnostic serum biomarkers complementing CA19.9 in detecting pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor with few biomarkers to guide treatment options. Carbohydrate antigen 19.9 (CA19.9), the most frequently used biomarker for PDAC, is not sensitive and specific enough for the detection of the disease. This study aimed to evaluate serum periostin (POSTN) and CA242 as potential diagnostic biomarkers complementing CA19.9 in detecting pancreatic cancer. Blood samples were from 362 participants, including 213 patients with different stages of PDAC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Most studies focussed on the capability of tumour marker to detect PDAC and therefore its potential for screening purposes (Ruckert et al 2010, Petrushnko et al 2016, Swords et al 2016. For instance, carbohydrate antigen variants, such as CA242, showed good potential for early pancreatic cancer detection (Dong et al 2018). Moreover, it was shown that another variant, CA125, had superior detection rates for irresectable disease in a cohort of 212 patients (Luo et al 2013), although its application is limited because a substantial proportion of patients with pancreatitis and jaundice also have increased serum CA125 levels (Ruckert et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focussed on the capability of tumour marker to detect PDAC and therefore its potential for screening purposes (Ruckert et al 2010, Petrushnko et al 2016, Swords et al 2016. For instance, carbohydrate antigen variants, such as CA242, showed good potential for early pancreatic cancer detection (Dong et al 2018). Moreover, it was shown that another variant, CA125, had superior detection rates for irresectable disease in a cohort of 212 patients (Luo et al 2013), although its application is limited because a substantial proportion of patients with pancreatitis and jaundice also have increased serum CA125 levels (Ruckert et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of POSTN gene in pancreatic stellate cells by transcriptome analysis spurred studies into its role in pancreatic cancer [ 12 ]. In particular, a 2018 clinical study of 287 participants [ 13 ] found that circulating levels of periostin were significantly higher in patients with pancreatic cancer than in healthy controls, and the advanced stage patients tended to have higher levels of periostin than the early-stage patients. Also, a 2017 clinical study of 80 patients with pancreatic cancer showed that those with high (vs. low) periostin expression had nearly two-times larger tumor volumes and suggested that periostin underlies the aberrant upregulation of pancreatic cancer cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…2B–D). Because cyclin D1 expression was proved to be positive correlated with cell proliferation, especially in carcinoma cells [28,29].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…By giving heat treatment for human pancreatic cancer cell line PANC-1, a tumor tissue model after heat stress was established, its proliferation rate was determined, and was compared with the control group. It was observed that the expression of Cyclin-D1 in the heat stress model increased, which indicates that the proliferation rate of pancreatic cancer cells subjecting to a heat radiation was increased, because some studies had testified that Cyclin-D1 related to the cell proliferation [28,29]. Since radiation causes an increase in the synthesis of heat shock proteins, thereby enhancing the endurance capacity of cells to heat radiation and increasing cell viability [35], we detected the changes in HSP70 expression after heating, and by pretreating the cells with HSP70 inhibitor VER-155008, it was determined that HSP70 plays an important role in the regulation of proliferation of pancreatic cancer cells subjected to a heat stress.…”
Section: Discussionmentioning
confidence: 99%